MENGIMPLEMENTASIKAN MATIUS 25:35 DALAM KEGIATAN JUM’AT BERKAH DI VERA LIMARDJO HOUSE OF MERCY - Steven, Steven; Mendrofa, Feri A.; Sihombing, Benjamin; Luaha, Khoisan L.N (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The Friday Blessing Program is a tangible manifestation of Jesus' teachings in Matthew 25:35, emphasising the importance of feeding the hungry as an expression of faith-based service. This program is carried out by Vera Limardjo House of Mercy (VL Home) under the auspices of the Cahaya Obor Berkat (COB) Foundation as a demonstration of social concern for underprivileged communities. The initiative involves the regular distribution of meals to those in need, aiming to enhance social well-being and foster a spirit of solidarity within the community. Implementing the Friday Blessing Program has received a positive response from various groups, including volunteers who willingly participate in this initiative. This positive reception indicates that the program not only benefits but also serves as a form of social education, encouraging the values of compassion and generosity among the broader society.It is hoped that through this program, the Batam community will be further motivated to share with others, even simple ways, such as offering a piece of bread or a spoonful of rice. Thus, the Friday Blessing Program is not merely a social initiative but also a concrete expression of the teachings of love in everyday life.